2019
DOI: 10.3390/cancers11040514
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Nutritional Index after Chemoradiotherapy Was the Strongest Prognostic Predictor among Biological and Conditional Factors in Localized Pancreatic Ductal Adenocarcinoma Patients

Abstract: Background: In many malignancies, including pancreatic ductal adenocarcinoma (PDAC), host-related inflammatory/immunonutritional markers, such as the prognostic nutritional index (PNI), modified Glasgow prognostic score (mGPS), and C-reactive protein (CRP)/albumin ratio are reported to be prognostic factors. However, the prognostic influence of these factors before and after chemoradiotherapy (CRT) has not been studied in PDAC patients. Methods: Of 261 consecutive PDAC patients who were scheduled for CRT with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 61 publications
0
23
0
Order By: Relevance
“…Moreover, these cytokines, including tumor necrosis factor (TNF), increase the transcapillary passage of albumin as well as the permeability of the microvasculature. As a consequence, serum levels of albumin will drop [ 50 ]. Fleck’s group has demonstrated an elevated albumin transcapillary escape rate in patients with either sepsis or cancer [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, these cytokines, including tumor necrosis factor (TNF), increase the transcapillary passage of albumin as well as the permeability of the microvasculature. As a consequence, serum levels of albumin will drop [ 50 ]. Fleck’s group has demonstrated an elevated albumin transcapillary escape rate in patients with either sepsis or cancer [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al reported that inflammatory and nutritional markers were independent predictive indexes for the survival of gastric cancer patients (14). Combined indexes of inflammation and nutrition, such as PNI (18,32), SIS (22,33), and AGR (16,34) have been proved to be related to survival in cancers. Consistently, our study suggested that low level of PNI and AGR and high level of SIS had poor OS and DFS in NPC patients.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical biochemistry-based indexes, such as prognostic nutritional index (PNI), albumin-to-alkaline phosphatase ratio (AAPR), albumin/globulin ratio (AGR), albumin (ALB), serum urea nitrogen (BUN) and creatinine (CREA) have been considered as independent prognostic factors for many cancers (15)(16)(17)(18)(19)(20)(21). The systemic inflammation score (SIS), based on the serum albumin level and LMR, has shown a better predictive effect on the prognosis of cancer compared to the single index (22).…”
Section: Introductionmentioning
confidence: 99%
“…Actually, the mGPS calculated by serum level of CRP and albumin could provide more accurate and comprehensive prognostic information than CRP alone [50,53]. Furthermore, a prognostic tool such as the mGPS is more reliable and reproducible.…”
Section: Discussionmentioning
confidence: 99%